ASSESSMENT OF HEAVY METAL CONCENTRATIONS IN GROUND WATER IN CRITICAL AREAS OF VISAKHAPATNAM CITY, AP, INDIA - Reddy, M. Sudhakar; Reddy, T. Byragi; Venkataramana, CH. (International Journal of Research -GRANTHAALAYAH, 2018)
Presence of heavy metal concentration in the ground water may cause health problems during intake of through different ways. Present study focused on heavy metal concentration of ground water in the sub-urban areas of Visakhapatnam City, AP, India. Most of heavy metals i.e., Aluminum (Al), Chromium (Cr), Manganese (Mn), Iron (Fe), Nickel (Ni), Zinc (Zn), Arsenic (As), Cadmium (Cd), Mercury (Hg) and Lead (Pb) were analyzed using Inductive Coupled Plasma Mass Spectroscopy (ICP-MS). Mean values of Zn (1.845) > Mn (1.203) > Fe (0.664) > Al (0.334) > Pb (0.245) > Ni (0.082) > Cr (0.066) > As (0.028) > Cd (0.012) > Hg (0.010) results respectively. Results shows that all heavy metal concentrations were exceeded the water quality permissible limit and this area were not suitable for domestic purpose and use before proper treatment.